Long‐Term Follow‐Up of Lateral Canthal Resuspension. Issue 2 (March 2018) - Ramesh, Sathyadeepak; Gupta, Adit; Rootman, Daniel Benson; Goldberg, Robert Alan
Abstract : Purpose: : To evaluate the long‐term results of lateral canthal resuspension over time. Design: : A cohort study of adults (n = 25, 45 eyelids) undergoing lateral canthal resuspension. Methods: : Marginal reflex distance 2 (MRD2), inferior scleral show, lateral canthal height, lateral canthal angle, horizontal palpebral aperture, and lateral scleral triangle area were measured preoperatively and at postoperative week 1, month 3, and the final follow‐up visit. Results: : Minimum follow‐up time was 6 months (mean, 15.1 months). At the final follow‐up visit, MRD2 decreased by 0.41 ± 0.14 mm, inferior scleral show decreased by 0.27 ± 0.05 mm, and lateral canthal height increased by 0.81 ± 0.15 mm. The overall function of time was found to be significant for change in MRD2 ( P < 0.01). In multiple comparisons, all time point values were significantly different from one another (Bonferroni corrected, P < 0.05), except for 3 months and the final position, which were not. Similarly, the overall effect of time on lateral canthus position was also significant ( P < 0.01). All time points were significantly different from one another (Bonferroni corrected, P < 0.05). The overall effect of time on inferior scleral show was also significant ( P < 0.01). Differences were significant from preoperative to final postoperative position, although the other time points were not significant (Bonferroni corrected, P < 0.05). No complications were noted. Conclusions: : Minimally invasive lateral canthal resuspension provides durable, albeit modest, improvements in MRD2, inferior scleral show, and lateral canthal height without significantly changing lateral canthal angle, horizontal palpebral aperture, or lateral scleral triangle area.